Detection of feline immunodeficiency virus in semen from seropositive domestic cats (Felis catus). - Jordan, H L (1995)
Electroejaculates from experimentally infected domestic cats were evaluated for the presence of feline immunodeficiency virus (FIV). Virus was isolated from cell-free seminal plasma and seminal cells by cocultivation with a feline interleukin-2-dependent CD4+ T-cell line, in which productive infection was demonstrated by syncytium formation and FIV gag p26 antigen secretion. In addition, an 868-bp segment of the FIV gag provirus gene was identified in cocultured cells by PCR and Southern analysis. A 582-bp fragment of the FIV gag provirus genome was detected by nested PCR and Southern analysis in nonfractionated seminal cells and in sperm purified by a swim-up procedure. This is the first report describing the detection of replication-competent FIV in cell-free and cell-associated forms in domestic cat semen.